Revisiting Virgil's Heroes' Parade: An Apocalyptic Historical Review. - Deutsch, Alon (Scripta Classica Israelica, 2025)
This paper reexamines the Heroes' Parade in Book 6 of Virgil's Aeneid through the lens of apocalyptic literature, specifically the 'historical apocalypse'. It seeks to reveal how Virgil recontextualizes common themes and motifs found within the apocalyptic genre to support Rome's imperial ideology. Drawing on a comparative analysis with the cloud vision in 2 Baruch, this study explores how both texts employ a divinely mediated review of history yet serve different purposes. While historical apocalypses typically offer consolation to oppressed communities, Virgil's account celebrates Rome's imperial destiny and proclaims the dawn of a new age--an era of salvation inaugurated by Augustus. Through this adaptation, the Aeneid transforms the Heroes' Parade into an imperial manifesto, positioning Augustus' reign as fulfilling a divine plan and elevating Rome's history to a transcendent, prophetic plane. In this way, the parade reinforces Augustus' legitimacy and Rome's preordained supremacy.